2012
DOI: 10.5897/ajar11.631
|View full text |Cite
|
Sign up to set email alerts
|

Policy options for improving market participation and sales of smallholder crop producers: A case study of the Free State Province of South Africa

Abstract: The paper identifies underlying factors behind farmers' market participation decisions and level of commercialisation of South African small scale farmers with a particular emphasis on transaction costs. The two-step decision making process is analyzed based on Agricultural Household Model that incorporates transaction costs using a Heckman selectivity procedure. The key importance of non price factors such as transaction costs over price factors come out clearly. Marginal effects are calculated and decomposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
(12 reference statements)
5
7
0
Order By: Relevance
“…The households who exploit larger pieces of land have the capacity to produce and sell more on the market than those endowed with a small plot size. This result confirms that of Bahta and Bauer (2012); Jagwe (2011) and Ouma et al (2010).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The households who exploit larger pieces of land have the capacity to produce and sell more on the market than those endowed with a small plot size. This result confirms that of Bahta and Bauer (2012); Jagwe (2011) and Ouma et al (2010).…”
Section: Resultssupporting
confidence: 80%
“…Household localized near a road increases the net gains from their sales on the market by 32 per cent. The same result was confirmed by the study of Bahta and Bauer (2012) in South Africa who found that having the access to a road increases the sales of 58 per cent. This result shows the advantage of the location near the agricultural access roads.…”
Section: Resultssupporting
confidence: 74%
“…Cooperatives have been found [55] to provide farmers with requisite platforms for exchanging information, and to serve as a link to buyers at a lower cost. These leads to improvements in their collective bargaining power and production capabilities [56,57], while invariably lowering the transaction costs due to market participation. A similar finding of the positive influence exerted by membership of farmer's cooperative or association has also been reported in [58,59].…”
Section: Effect Of Identified Variables On Market Participationmentioning
confidence: 99%
“…This variable was included as a dummy variable if any of the household members had a membership in the farmers' organization. Membership of the farmers' organization has been found to increase market participation of households because it improves the capabilities of farmer production and marketing [31]. In this study, we assumed that membership of a farmer organization positively influenced both the probability of market participation and the quantity of rice sold among smallholder farmers in Myanmar.…”
Section: Membership In a Farmer Organizationmentioning
confidence: 99%